FORMATION OF COMMUNICATION CULTURE BASED ON DIALOGUES IN AN ENGLISH LESSON IN A HIGHER EDUCATIONAL INSTITUTION (Journal of Science-Innovative Research in Uzbekistan, 2024)
This paper examines various non-traditional forms teaching a foreign language, which contribute to increasing internal motivation. In our opinion, non-traditional forms of foreign language teaching languages have a number of advantages according to certain criteria in comparison with traditional.